STUDY HYGIENE OPERATOR DAN SANITASI TERHADAP KUALITAS BAKTERIOLOGIS AIR MINUM ISI ULANG DI KOTA JAMBI - Gustomo Yamistada; Sukmal Fahri; Jessy Novita Sari (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
Efficiency efforts by the management of drinking water refill depot (DAMIU) in Jambi leadmanagers of drinking water refill depot did not pay attention to the sanitary condition of drinking water refilldepot and the cleanliness of the operator's hand, hygienic behavior such as nails and clothes are notclean. This allows the quality of produced water refill ineligible particular requirements of bacteriologicalcontamination is suspected. The purpose of this study is known picture of the bacteriological quality(coliform), the relationship hygiene and sanitation depot operators of drinking water against coliformnumbers of refill drinking water in the city of Jambi. This research is descriptive analytic using crosssectional design.Samples in this study is 40 samples. Analysis conducted between variables using ChiSquare test.The results showed coliform numbers refillable water that qualifies as many as 28 (70%) andnon-qualified 12 (30%). The analysis showed there is a significant relationship between hygiene operatorwith the number of coliform value of p - value 0,037, there are behaviors that are inconsistent with theoperator Kepmenperindag No. 651/MPP/kep/10/2004. There is a relationship sanitation depot refilldrinking water with coliform numbers p value - value of 0.011 (p <0.05>, still found depot refill drinkingwater with limited sanitation facilities and drinking water are still merging with home depot and are not yeteligible in accordance Kepmenperindag No. 651/MPP/kep/10/2004.It is suggested to DAMIU manager tosupervise the operator hygiene and sanitation factors noticed depot refill drinking water.